Photocatalytic activity of silver-doped titanium dioxide on methyl orange degradation: effect of pH / Muhammad Amirul Shafik Zainal Abidin - Zainal Abidin, Muhammad Amirul Shafik (2018)
The photocatalytic activity of silver (Ag) deposited titanium dioxide (TiO2) in the photodegradation of methyl orange (MO) was investigated. The bare TiO2 and the Ag-doped TiO2 was successfully synthesized by wet impregnation method. The photocatalysts were characterized using XRD, FESEM, BET, FTIR, BET, Malvern particle and EDX. The results show the crystal structure of bare TiO2 and Ag doped TiO2 to be an anatase structure. The FESEM image of both samples shows some square-like and spherical shapes in various sizes. In EDX analysis, the Ag nanoparticles are uniformly dispersed in the TiO2 nanoparticles. In FTIR analysis, the peaks observed for both bare TiO2 and Ag-doped TiO2 powder were almost the same at 1737 and 3500 cm-1 respectively. The surface area of bare TiO2 and 5wt% of Ag-doped TiO2 were 9.71 and 9.32 m2/g, respectively. UV-Vis spectrophotometer was used to determine the wavelength and band gap energy of bare TiO2 and Ag-doped TiO2. It founded that the wavelength for both photocatalyst samples giving the same results which is 374 nm although Ag was added into TiO2 particle. The photocatalytic degradation on methyl orange under UV light irradiations was studied at different pH value of MO solution. The results show that the Ag-doped TiO2 enhanced the photodegradation of MO dye in all the pH range studied. In addition, the optimum pH for both photocatalysts is at 2 with 98% removal efficiency for Ag-doped TiO2. Therefore, it can be concluded that Ag-doped TiO2 has a great potential for dye removal under favorable pH condition.